Gestión eficiente de almacenes temporales y su impacto en la optimización del despacho aduanero en Huaquillas - Reyes Saritama, Ruth Esperanza (Machala : Universidad Técnica de Machala, 2025)
The present essay analyzes the efficient management of temporary warehouses and its impact on customs clearance in Huaquillas, Ecuador. It highlights that these facilities play a strategic role in the logistics chain by facilitating the custody, control, and nationalization of goods. However, limitations in infrastructure, digitalization, manual processes, and institutional coordination are identified, which generate delays and higher operating costs. The study, using a mixed-methods approach, combines semi-structured surveys applied to 30 actors in foreign trade (administrators, carriers, and customs officials) with documentary review. The results show that although 60% perceive the infrastructure as adequate, 67% consider clearance times to be slow, and 70% observe deficient inter-institutional coordination. Likewise, two-thirds of respondents rated the quality of service as inefficient. The main difficulties identified are bureaucracy, lack of equipment, and insufficiently trained personnel. Among the proposed improvements are automation, digital traceability, the use of technologies such as WMS, RFID, and blockchain, as well as periodic coordination meetings and collaborative platforms. International cases, such as reforms in Peru, Chile, and Mexico, show that technological modernization and staff training strengthen logistics competitiveness. In conclusion, the work confirms that the efficiency of temporary warehouses directly affects the speed and quality of customs clearance. Investment in infrastructure, digitalization, continuous training, and institutional coordination is recommended to optimize the logistics system in Huaquillas.
El presente ensayo analiza la gestión eficiente de los almacenes temporales y su impacto en el despacho aduanero en Huaquillas, Ecuador. Se resalta que estos depósitos cumplen un rol estratégico en la cadena logística al facilitar la custodia, control y nacionalización de mercancías. Sin embargo, se identifican limitaciones en infraestructura, digitalización, procesos manuales y coordinación institucional, que generan demoras y mayores costos operativos. El estudio, con enfoque mixto, combina encuestas semiestructuradas aplicadas a 30 actores del comercio exterior (administradores, transportistas y funcionarios aduaneros) y revisión documental. Los resultados muestran que, aunque el 60% percibe la infraestructura como adecuada, un 67% considera lentos los tiempos de despacho y un 70% observa deficiente coordinación interinstitucional. Asimismo, la calidad del servicio es calificada como ineficiente por dos tercios de los encuestados. Las principales dificultades identificadas son la burocracia, la falta de equipamiento y personal capacitado. Entre las mejoras propuestas destacan la automatización, trazabilidad digital, uso de tecnologías como WMS, RFID y blockchain, así como reuniones periódicas de coordinación y plataformas colaborativas. Casos internacionales, como las reformas en Perú, Chile y México, evidencian que la modernización tecnológica y la capacitación del personal fortalecen la competitividad logística. En conclusión, el trabajo confirma que la eficiencia de los almacenes temporales incide directamente en la rapidez y calidad del despacho aduanero. Se recomienda invertir en infraestructura, digitalización, capacitación continua y coordinación institucional para optimizar el sistema logístico en Huaquillas."
Keywords: ALMACENES TEMPORALES; DESPACHO ADUANERO; LOGÍSTICA; DIGITALIZACIÓN